Orexin A and orexin receptor 1 axonal traffic in dorsal roots at the CNS/PNS interface - Colas, Damien; Manca, Annalisa; Mourrain, Philippe (Frontiers in Neuroscience, 2014)
Hypothalamic orexin/hypocretin neurons send long axonal projections through the dorsal spinal cord in lamina I-II of the dorsal horn at the interface with the peripheral nervous system (PNS). We show that in the dorsal horn OXA fibers colocalize with substance P (SP) positive afferents of dorsal root ganglia (DRG) neurons known to mediate sensory processing. Further, OR1 is expressed in p75NTR and SP positive DRG neurons, suggesting a potential signaling pathway between orexin and DRG neurons. Interestingly, DRG sensory neurons have a distinctive bifurcating axon where one branch innervates the periphery and the other one the spinal cord (pseudo-unipolar neurons), allowing for potential functional coupling of distinct targets. We observe that OR1 is transported selectively from DRG toward the spinal cord, while OXA is accumulated retrogradely toward the DRG. We hence report a rare situation of asymmetrical neuropeptide receptor distribution between axons projected by a single neuron. This molecular and cellular data are consistent with the role of OXA/OR1 in sensory processing, including DRG neuronal modulation, and support the potential existence of an OX/HCRT circuit between CNS and PNS.